Pembuatan TREPOS (Travel Protection System) Sebagai Upaya Penurunan Travel Dispatch pada Small Excavator - Isyanto, Muhamad Sandi Isyanto; Sugiyanto, Sugiyanto; Bahiuddin, Irfan; Ismail, Andi Akhmad; Khaerudin, Arif; Muslih, Imam (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2025)
Excavators primarily perform digging, loading, and swinging operations, while travel operations are intended to support mobility within the work area and should not exceed the primary operations. The operational data of the PC210-10M0 excavator, accessed through KOMTRAX, was utilized in this study as part of Komatsu's monitoring service. The objective was to design, develop, and install a travel protection system (TREPOS) and analyze travel dispatch data as an indicator of travel operations. The TREPOS development process included system design, wiring diagram creation, assembly, installation, and system testing. TREPOS employs a Programmable Logic Controller (PLC) to process inputs and outputs. Its function is to provide an audible warning and reduce the engine speed to low idle if the travel operation exceeds 15 minutes. The PDCA method was used in travel dispatch data analysis as an evaluation tool for TREPOS development. Initial results indicated no reduction in travel durations exceeding 20 minutes, necessitating further improvements. The second installation showed a reduction in the number of travel durations exceeding 20 minutes from 13 to 8 occurrences.